الإبداع عند أبي الحسن المسعودي في دراسة تاريخ الأديان (Abu al-Ḥasan al-Masʿūdī’s Creativity in Studying History of Religions) - إلياس, مجدان; عبد الجليل, محمد نوح (Journal of Islam in Asia (E-ISSN 2289-8077), 2018)
الملخّص من مميّزات إسهامات أبي الحسن المسعودي في دراسة التاريخ البشري تحليلاته للمواد التاريخية وعرضها كوحدات موضوعية منظمة، وقد سماه البعض "هيرودوتس العرب". اعتنت هذه الدراسة بالكشف عن جوانب الإبداع عنده في دراسة تاريخ الأديان، وانتهج الباحث منهج الاستقراء والتحليل في تناوله للنصوص من المؤلَّفين الأساسيين للمسعودي وهما كتاب "مروج الذهب ومعادن الجوهر" وكتاب "التنبيه والإشراف". وكذلك استخدم الباحث منهج التحليل التاريخي في الكشف عن الجوانب التاريخية للأديان التي تناولها المسعودي. وقد توصل الباحث إلى أن للمسعودي إبداعات في منهج جمع المعلومات وقبول الأخبار عن أديان غير الإسلام، وله إبداعات كذلك في منهج المقارنة والتحليل وتصنيف أديان العالم. الكلمات المفتاحيّة: الإبداع، تاريخ الأديان، مشاهدة العيان، الموضوعية، فلسفة الدين، تصنيف الأديان. Abstract One of the remarkable features contributed by Abu al-Ḥasan al-Masʿūdī to the study of human history is his analysis of the historical materials and their presentation as organized subjective units. Some even nicknamed al-Masʿūdī as “Herodotus of the Arabs.” This study examines his creativity in study of the history of religions. Using analytical and inductive methodology, the researcher deals with al-MasʿūdÊ’s two primary works, namely: Murūj al-Dhahab wa Maʿādin al-Jawhar (The meadows of Gold and Mines of Gems), and Kitāb al-Tanbīh wa al-Ishrāf (The Book of Notification and Verification). In addition to that, the researcher applied historical analysis to uncover the historical aspects of religions under al-Mas’ūdī’s study. The research finds that al-Mas’ūdī employed creative methods to gather and accept information about religions other than Islam. He also demonstrated creative methods of comparison, analysis and classification of world religions. Keywords: Creativity, history of religions, eye witness, objectivity, philosophy of religion, classification of religions.